Curcumin ameliorates oxaliplatin-induced allodynia response and melanocortin downregulation in the spinal cord - Alma Nuril Aliya; Luke Wongso; Diah Ayu Wakita Trimanda; Risda Maulida; I Nengah Budi Sumartha; Samirah Samirah; Abdulloh Machin; Long Chiau Ming; Abdelhakim Bouyahya; Mahardian Rahmadi; Junaidi Khotib; Сhrismawan Ardianto (Research Results in Pharmacology)
Introduction: Oxaliplatin is a platinum-based chemotherapy agent that often causes chemotherapy-induced peripheral neuropathy (CIPN). This effect limits the potential activity and decreases the cancer patient’s quality of life. Melanocortin and transient receptor potential ankyrin 1 (TRPA1) pathways are believed to be essential in recruiting an allodynia response. Based on previous studies, curcumin has shown antioxidant and anti-inflammatory activities that could potentially be useful for decreasing the allodynia effects of oxaliplatin treatment. This study investigated the effect of curcumin on CIPN conditions. In addition, we further elaborated to measure the involvement of spinal melanocortin and the TRPA1 system.